Propuesta de un sistema de gestión administrativo y financiero para la Liga Deportiva Cantonal de Mejía de la ciudad de Machachi. - Chancúsig Chuquilla, Jenny del Rocío (2011)
This work of investigation is focused on a proposal of an administrative and financial management system for sport league of Canton Mejia in Machachi city. Because of there are no administrative and financial procedures the league of Mejia has suffered dilays in administrative institutional management. These dilays have provoked a lack of organization in sport activities, a lack of budget in the distribution of economical resources. This has caused distrust and low credibility in the management and strengthening sport. The type of research that was used: descriptive, documental and field. The universe of population of studio was formed by leaders, institutional personnel and sportmen and sportwomen. The results gotten have shown the league of Mejia doesn’t use a strategic plan and doesn´t have a manual of functions and procedures to reduce human, economical and material resources with effectiveness and efficacy. Those arguments droven to design an administrative and financial management system. The most important aspects are: planifications, organizations, execution and control to facilitate tools to the leaders, institutional personnel and sportmen and sportwoman to let them an effective development of their activities and reach objectives. At the same time. It helps them to take decisions to benefit the sport in Canton Mejia.